2020
DOI: 10.1155/2020/1630102
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of YuPingFeng in the Treatment of COPD Based on Network Pharmacology

Abstract: YuPingFeng (YPF) granules are a classic herbal formula extensively used in clinical practice in China for the treatment of COPD. However, the pathological mechanisms of YPF in COPD remain undefined. In the present research, a network pharmacology-based strategy was implemented to elucidate the underlying multicomponent, multitarget, and multipathway modes of action of YPF against COPD. First, we identified putative YPF targets based on TCMSP databases and constructed a network containing interactions between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The main mechanisms of the antihypertensive effects of Uncaria alkaloids have been shown by the authors, and they also recognized a potential application for the potent chemicals in the treatment of Alzheimer’s disease. YuPingFeng (YPF) granules are a classic herbal formula widely utilized in clinical practice in China against chronic obstructive pulmonary disease (COPD ) , which has been investigated by Yin and co-workers using network pharmacology analysis . This finding suggested that the therapeutic effects of YPF in treating COPD might be contingent on the response to steroid hormones, glucocorticoids, and pathways connected to HIF-1 and apoptotic signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main mechanisms of the antihypertensive effects of Uncaria alkaloids have been shown by the authors, and they also recognized a potential application for the potent chemicals in the treatment of Alzheimer’s disease. YuPingFeng (YPF) granules are a classic herbal formula widely utilized in clinical practice in China against chronic obstructive pulmonary disease (COPD ) , which has been investigated by Yin and co-workers using network pharmacology analysis . This finding suggested that the therapeutic effects of YPF in treating COPD might be contingent on the response to steroid hormones, glucocorticoids, and pathways connected to HIF-1 and apoptotic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of network pharmacology to explore the potency of the natural compound has been performed by a few research teams. Network pharmacology was used by Sakle and co-workers to look into the possible targets of Caesalpinia pulcherima . The authors suggested that four active compounds from the plant are potential drugs in breast cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the “network pharmacology” approach coupled with other in‐silico methods was performed to determine the potency of active compounds of Brucea javanica in treating the hypertension [17–20] . Several integrated analytical schemes, including target prediction, protein‐protein interaction (PPI), and gene enrichment analysis, were performed to identify the critical protein corresponding to the increase of blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The YuPingFeng formula consists of three herbs: Radix Astragali (Huang Qi (HQ)), Rhizoma Atractylodis Macrocephalae (Bai Zhu (BZ)), and Radix Saposhnikoviae (Fang Feng (FF)). A previous study [ 13 ] found that YPF is effective for treating chronic obstructive pulmonary disease (COPD), and the researchers explored the potential mechanisms behind the curative effects of the drug based on network pharmacology technology. A recent study has indicated that YPF is beneficial for relieving the relapse of asthma induced by house dust mites [ 14 ].…”
Section: Introductionmentioning
confidence: 99%